Matriconditioning effect on the physiological performance of chia seeds (Salvia hispanica L.) - Adriane Witkovski; Alberto Ricardo Stefeni; Jean Carlo Possenti; Adriana Bezerra de Lima; Cristiane Deuner; Vitor Rampazzo-Favoretto (Revista de Ciencias Agrícolas, 2022)
Solid matrix priming (matriconditioning) permits slow seed hydration, and germination and emergence period reduction. In general, seeds need to be soaked to start their germination process. The objective of this study was to evaluate the effect of the matriconditioning under the imbibition curve and the physiological performance of two lots of chia seeds with different qualities. The study was performed with chia seeds harvested by small-scale farmers. To estimate the imbibition curve, seeds from both lots were started in the imbibition process on a stainless-steel screen placed in plastic boxes, containing 55.5 grams of sterilized vermiculite and moisturized with distilled water at 100% of their retention capability. The imbibition curve weights were made 0, 2, 4, 8, 16, and 32 hours after the process had started. Simultaneously, in each evaluation period, seeds were submitted to the following tests: germination, first count of germination, plantlet shoot, root and total lengths, emergence velocity index and average time, and accumulated emergence. A completely randomized experimental design was used. It was possible to conclude that the beginning of phase II of germination in matriconditioned seeds varies in function of the chia seeds' lot quality. The matriconditioning contributes to the physiological performance, increasing and accelerating plantlets' emergence.